Tuberculosis of the Vulva - Kitisupornpun, Somyod; Mahanupab, Pongsak; Intapibool, Suntorn (Biomedical Sciences and Clinical Medicine, 2024)
Genital tract tuberculosis is usually secondary to haematogenous spreading from pulmonary or other nongenital tract foci. The most frequent sites of tuberculous involvement in the female genital tract are the fallopian tubes and endometrium, although the cervix and ovary also can be affected. The vagina and vulva are rarely involved. In this report, the authors present a case of chronic ulcerative lesion at the introitus. The patient was treated with various antibiotics, but the ulcer persisted. Tissue biopsy showed typical (classical) tuberculous granuloma and positive acid fast bacilli, which confirmed the diagnosis. Chest x–rays showed infiltration of the right upper lobe. It was planned to treat the patient with antituberculous drugs for 6 months. The result was very good after 6 weeks. In conclusion, this is an example of a rare form of genital tuberculosis, which had good response to antituberculous drugs after long-standing treatment of various antibiotics.